Atividade de enzimas que degradam nucleotídeos e nucleosídeo da adenina em linfócitos de gestantes soropositivas para toxoplasmose - Bertoldo, Tatiana Montagner Dalcin (2013)
Toxoplasmosis, caused by the intracellular protozoan Toxoplasma gondii is an infectious disease, and this triggers the activation of the immune system. The pregnancy, in turn, shows characteristics of systemic inflammatory response. The ecto-enzymes as E-NTPDase and E- ADA activities in addition to possessing important in regulating the levels of adenine nucleotides and nucleoside, have shares extremely important in the immune system. Thus, the aim of this study was to determine the activity of enzymes that degrade adenine nucleotides and nucleoside in lymphocytes of women with antibodies to Toxoplasma gondii. Were included in the study, pregnant women seropositive (immune) and seronegative (susceptible) to toxoplasmosis in the last trimester of pregnancy, previously diagnosed service prenatal HUSM. Also, non-pregnant women seropositive and seronegative for toxoplasmosis, in the period from March to December 2012. We determined the enzymatic activities of ecto-enzymes: E-NTPDase and E-ADA in lymphocytes of pregnant and non-pregnant. The results showed an increase of the E-NTPDase activity and may lead to decreased levels of nucleotides ATP and ADP, and an increase in the activity of E-ADA, which may cause a decrease in the concentration of adenosine in groups: III (seronegative pregnant women toxoplasmosis) and IV (seropositive pregnant women for toxoplasmosis) when compared to the control group (I: non-pregnant women seronegative for toxoplasmosis). Pregnant women seropositive for toxoplasmosis compared with seronegative pregnant women did not change, thus revealing that toxoplasmosis in its chronic phase, may not interfere with purinergic signaling. In conclusion, the third trimester of pregnancy appears to be a physiological condition that involves purinergic signaling and toxoplasmosis in its chronic phase does not seem to be able to change this signaling.